Applications of electrochemical sensors and biosensors based on modified screen-printed electrodes: a review. Issue 12 (10th March 2020) - Beitollahi, Hadi; Mohammadi, Sayed Zia; Safaei, Mohadeseh; Tajik, Somayeh
Abstract : The focus of this report is electroanalysis performed via screen-printed electrodes. Abstract : The focus of this report is electroanalysis performed via screen-printed electrodes. All the basic characteristics required in this field are taken into account, including the fundamental assessments of screen-printed materials used as electrodes, the use of testing electrode prototypes in the laboratory, fundamental and progressive studies on different electrode fabrication procedures, and their practical uses in quantifying biological species, pharmaceutical compositions, environmental contaminants and heavy metals. The last case is presented as a set of comprehensive tables that show an overall summary of the published approaches. Lastly, current trends and significant achievements are delineated along with future options.